2022
DOI: 10.1007/s13197-022-05578-y
|View full text |Cite
|
Sign up to set email alerts
|

Capsicum fruits as functional ingredients with antimicrobial activity: an emphasis on mechanisms of action

Abstract: Capsicum spp. fruits (CFs) are a basic ingredient in the diet and have been used as active ingredients in the pharmaceutical, cosmetic, and food products, due to their antioxidant, anti-inflammatory, antiseptic, and antimicrobial properties. The antimicrobial activity is the most studied property due to its effectiveness against pathogenic species, however, few studies have focused on the mechanisms of action involved. Therefore, this review discusses the effects generated by the CFs compounds on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…BRS Moema (Tables 1–3) and the potential uses of Capsicum spp. fruits to prevent oxidative damage and treat antimicrobial infections, 48,49 the lack of the antiproliferative effect might suggest low toxicity of C. chinense var. BRS Moema against normal tissues that normally present a high proliferative rate such as skin, mucosa, and bone marrow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BRS Moema (Tables 1–3) and the potential uses of Capsicum spp. fruits to prevent oxidative damage and treat antimicrobial infections, 48,49 the lack of the antiproliferative effect might suggest low toxicity of C. chinense var. BRS Moema against normal tissues that normally present a high proliferative rate such as skin, mucosa, and bone marrow.…”
Section: Resultsmentioning
confidence: 99%
“…BRS Moema (Tables 1-3) and the potential uses of Capsicum spp. fruits to prevent oxidative damage and treat antimicrobial infections, 48,49…”
Section: Antiproliferative Activity Evaluationmentioning
confidence: 99%
“…It has been demonstrated that capsaicinoids and other phenolic compounds inhibited growth of microorganism like bacteria, yeasts, and fungi [121]. Capsaicin could inactivate the virus binding proteins and prevent their replication [121].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…It has been demonstrated that capsaicinoids and other phenolic compounds inhibited growth of microorganism like bacteria, yeasts, and fungi [121]. Capsaicin could inactivate the virus binding proteins and prevent their replication [121]. Previous reports supported that capsaicin showed strong antimicrobial activities against Streptococcus pyogenes, E. coli, S. aureus, Proteus mirabilis, Proteus vulgaris, P. aeruginosa, Enterobacter aerogenes and S. mutans.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Capsaicin and its analogues have been proven to exhibit antimicrobial activity against phytopathogens, such as the fungus Botrytis cinerea, Aspergillus niger, Colletotrichum capsici, Fusarium oxysporum, or Rhizoctonia solani [112,114,126,127]. Although capsaicinoids and capsinoids from pepper extracts are natural products that can be applied to control pathogenic fungi growth in plant crop production, it is important to understand the effect these compounds could have on species sharing the same environment [128]. In fact, in agricultural production, capsaicinoid molecules can play a dual role as biocidals.…”
Section: Impact Of Using Capsaicinoids and Capsinoids On Environmenta...mentioning
confidence: 99%